2009
DOI: 10.1007/s12012-009-9038-2
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiac Effects of Prolonged Vitamin B12 and Folate Deficiency in Rats

Abstract: In the recent past, hyperhomocysteinemia (HHCY) has been linked to chronic heart failure. Folate and vitamin B12 deficiencies are the common causes of HHCY. The impact of these vitamins on cardiac function and morphology has scarcely been investigated. The aim of this study was to conduct an analysis of the cardiac effect of folate and vitamin B12 deficiency in vivo. Two groups of rats, a control (Co, n = 10) and a vitamin-deficient group (VitDef, n = 10), were fed for 12 weeks with a folate and vitamin B12-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…First, nutrients act as a source of methyl groups or as co-enzymes for one-carbon metabolism that regulates methyl transfer (6) . B-vitamins including folate, vitamin B 12 , vitamin B 6 and vitamin B 2 are involved as coenzymes with methionine, choline, betaine and serine as methyl donors for DNA methylation and histone methylation (7) . Second, nutrients and bioactive food components can directly affect enzymes that catalyse DNA methylation and histone modifications (4) .…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…First, nutrients act as a source of methyl groups or as co-enzymes for one-carbon metabolism that regulates methyl transfer (6) . B-vitamins including folate, vitamin B 12 , vitamin B 6 and vitamin B 2 are involved as coenzymes with methionine, choline, betaine and serine as methyl donors for DNA methylation and histone methylation (7) . Second, nutrients and bioactive food components can directly affect enzymes that catalyse DNA methylation and histone modifications (4) .…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“… 40 , 41 Vitamin B12 deficiency will also result in HHcy because re-methylating Hcy to methionine is reduced, cannot transfer, which influences the production of methionine and regeneration of tetrahydro-folic acid. 42 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been reported on the impact of vitamin B12 on cardiovascular system. Taban-Shomal et al [23] studied "the cardiac effects of prolonged vitamin B12 and folate deficiency in rats". They found that fractional shortening, LV dimension at end-diastole and end-systole, posterior wall thickness, perivascular collagen, mast cell number, and natriuretic peptide tissue levels were comparable in vitamin deficiency and control animals.…”
Section: Discussionmentioning
confidence: 99%